2020
DOI: 10.33824/pjpr.2019.34.4.39
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Indigenous Perceived Favouritism Scale for University Students

Abstract: The aim of the study was to develop an indigenous scale on the phenomenon of perceived favouritism among university students. A list of 98 items was compiled after reaching saturation level by interviewing 25 university students of BS, individually. Then redundant items were excluded and 39 items were retained. For empirical validation, five experts were approached and after empirical validation, a scale of 38 items was prepared. The pilot study was conducted on 25 university students of BS and revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…National-level (Fernández et al 2022;Madolell et al 2020) and international studies have confirmed this idea. In fact, the evidence indicates that female university students are more sensitive to questions of gender (Khan et al 2018). It is reasonable to think that female and non-binary students do less to propagate stereotypes, as they are the groups that suffer most from the prejudice and stigma that these beliefs produce.…”
Section: Discussionmentioning
confidence: 99%
“…National-level (Fernández et al 2022;Madolell et al 2020) and international studies have confirmed this idea. In fact, the evidence indicates that female university students are more sensitive to questions of gender (Khan et al 2018). It is reasonable to think that female and non-binary students do less to propagate stereotypes, as they are the groups that suffer most from the prejudice and stigma that these beliefs produce.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many methods for choosing the sample size, in this research, Cochran's sample size determination formula was used (Khan et al, 2018). From the statistical population of 6714 total students of Bamyan University, 130 females equal to 35.8%, and 233 males equal to 64.2% with a confidence level of 95% and considering a 5% degree of error, the statistical sample size is equal to 363 students of Bamyan University.…”
Section: Methodsmentioning
confidence: 99%
“…The selection of the socio-demographic variables was based on the literature which studied in this study and the questionnaire of (Khan et al, 2018;Tiwari et al, 2018). these included variables such as Age, Gender, Grade, Faculty, marital status, family type, and some other determinant of gender inequality in Bamyan society.…”
Section: Methodsmentioning
confidence: 99%
“…The survey instrument integrates questions adapted from various studies. Questions for the independent variable, favoritism, were extracted from the questionnaire presented by Ehsaan & Naz (2019). Their study identi􀅫ied three factors, and we included only the important questions from the third factor, which is discrimination.…”
Section: Methodsmentioning
confidence: 99%